Polylactic acid conductive master batch, preparation method and polylactic acid conductive fiber
By using the combination of low-melting point branched polylactic acid and conductive powder, high-conductivity and high-strength polylactic acid conductive fibers are prepared, which solves the poor toughness and spinability problems of polylactic acid materials, and realizes the polylactic acid conductive fibers. Low resistance and high strength to achieve performance indicators similar to polyester or nylon conductive fibers.
Patent Information
- Application Number
- CN202411295520.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to prepare high-conductivity and high-strength polylactic acid conductive fibers, and the polylactic acid material has poor toughness, slow crystallization rate and poor spinning properties, resulting in high resistance and low strength of the conductive fibers, which cannot reach polyester or Performance indicators of nylon conductive fibers.
Polylactic acid conductive masterbatches, including carbon black type and metal oxide type, are prepared by using low melting point branched polylactic acid powder, coupling agent, dispersion modifier, The combination of antioxidants and lubricants improves the compatibility and flowability of conductive powders, and uses a two-component composite spinning process to prepare conductive fibers.
The low resistivity and high strength of polylactic acid conductive fibers are achieved, with resistance less than 20Ω·cm, fiber strength is 2-2.8cN/dtex, and elongation of breaking is 30-150%, which solves the fluidity and ability of polylactic acid conductive fibers. Spinning problem improves spinning orientation and drafting effect.
Smart Images

Figure CN119220073A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite spinning conductive fibers, and in particular to a polylactic acid conductive masterbatch, a preparation method and polylactic acid conductive fibers manufactured from the masterbatch. Background Art
[0002] Polylactic acid (PLA) is a non-toxic, fully biodegradable polymer with good chemical inertness, easy processing and good biocompatibility. It does not pollute the environment and is considered to be the most promising environmentally friendly polymer material. Polylactic acid fibers can be prepared by traditional spinning processes (such as wet spinning, melt spinning, electrospinning, etc.) and can be produced on an industrial scale. With the continuous reduction of costs, the production scale of polylactic acid and its fibers has expanded year by year, and the melt spinning technology of PLA has also been basically mature. PLA is expected to replace petroleum-based polymer materials as the raw material of chemical fibers to solve the resource shortage and environmental pollution problems faced by the development of synthetic fibers. However, the research and development of the functionalization of PLA fibers has not made much progress. For example, the conductive functionalization of fibers cannot reach the performance indicators similar to those of polyester or nylon conductive fibers due to technical reasons, and its practicality is poor.
[0003] The conductive fibers used in industry are mainly polyester or nylon conductive fibers. Due to the percolation threshold conductive mechanism, they are generally made by double-combination composite spinning of conductive masterbatches with high content of conductive agents. The conductive fibers made in this way can significantly reduce their resistance due to the concentration of conductive agents. For example, when the conductive carbon black in polyester conductive masterbatches is added at more than 30%, with the help of efficient composite spinning equipment, it is possible to produce, for example, 20D conductive fibers with a resistance of 10 6 Ω / cm, polyester conductive fiber with a strength of more than 2.5cN / dtex.
[0004] The characteristics of polylactic acid are slow crystallization speed and high brittleness before effective stretching. When the conductive masterbatch made of PLA slices, conductive materials and dispersants and lubricants commonly used to make conductive masterbatch are used as additives, the melt has a slow orientation crystallization speed after coming out of the spinneret, the strength is slow to increase, the spinning speed is slow, and the spinnability is poor. The polylactic acid conductive fiber prepared by the existing technology cannot meet the requirements of high-conductivity polylactic acid conductive fiber. For example, Publication No. CN105839397B uses surface reaction to prepare cuprous sulfide / polylactic acid composite conductive fiber; Publication No. CN103243563B uses polyvinyl alcohol to make PLA fiber porous, and then reacts polyaniline in situ to obtain conductive polyaniline polylactic acid conductive fiber; Publication No. CN105113047B uses conductive agent and PLA to prepare spinning solution and uses electrospinning process to obtain nano gold PLA conductive fiber; Publication No. CN10 2943315B uses poly (vinyl acetate-co-vinyl alcohol) (P(VAC-Co-VA)) as a dispersant and conductive carbon black as a conductive agent to prepare a PLA conductive masterbatch, and then adopts a melt composite spinning method. Due to the small amount of conductive agent added, the conductivity index does not meet the requirements; Publication No. CN106676679A uses a conductive filler and polyvinyl acetate (PVAc) added to a solvent to prepare a dispersion of the conductive filler, and the conductive agent is combined with the fiber surface by a method similar to dyeing to obtain PLA conductive fibers.
[0005] In order to improve the problems of poor toughness, slow crystallization rate and spinnability of PLA, attempts have been made to improve it, such as adding polybutylene succinate (PBS). When 20% PBS is added to PLA, the impact strength of the material can be increased by 7 times, the drawing properties of the primary fiber are improved, and thus the spinnability can also be improved. However, PBS and PLA are two thermodynamically incompatible substances, which have an adverse effect on the strength of the fiber product.
[0006] The masterbatch made by using masterbatch manufacturing additives similar to polyester or nylon cannot be spun normally due to lack of melt strength and slow crystallization speed. After the melt comes out of the composite spinneret, it cannot reach the process of spinneret stretching-orientation-crystallization-rapid strength improvement. Similarly, the existing modification technology for polylactic acid is not suitable for the modification of polylactic acid conductive masterbatch and the improvement of spinning effect. Summary of the invention
[0007] The purpose of the present invention is to solve the above-mentioned technical problems and provide a polylactic acid conductive masterbatch, a preparation method and a polylactic acid conductive fiber made from the masterbatch. Low-melting-point branched polylactic acid is used as a dispersing aid and compatibilizer. The prepared polylactic acid conductive masterbatch has good fluidity and high conductivity. It is completely compatible with polylactic acid and has good compatibility with conductive powder.
[0008] In order to achieve the above technical objectives and meet the above technical requirements, the technical solution adopted by the present invention is: a polylactic acid conductive masterbatch, which is prepared from raw materials including polylactic acid powder, conductive powder, coupling agent, dispersing modifier, antioxidant and lubricant, and the polylactic acid conductive masterbatch includes carbon black type polylactic acid conductive masterbatch and metal oxide type polylactic acid conductive masterbatch.
[0009] The carbon black type polylactic acid conductive masterbatch comprises polylactic acid powder, conductive carbon black powder, aluminate coupling agent, dispersing modifier, 1010 antioxidant, and stearic magnesium lubricant, and the weight percentage of each component is: polylactic acid powder 60-75%, conductive carbon black powder 20-35%, aluminate coupling agent 0.2-1%, dispersing modifier 2-6%, 1010 antioxidant 0.1-0.5%, and stearic magnesium lubricant 2-4%; The metal oxide type polylactic acid conductive masterbatch comprises polylactic acid powder, conductive metal oxide powder, aluminate coupling agent, dispersing modifier, 1010 antioxidant, and magnesium stearate lubricant, and the weight percentage of each component is: polylactic acid powder 25-45%, conductive metal oxide powder 50-70%, aluminate coupling agent 0.2-1%, dispersing modifier 1-4%, 1010 antioxidant 0.1-0.5%, and magnesium stearate lubricant 1-2%.
[0010] Preferably, the dispersing modifier is low-melting-point branched polylactic acid, the resistivity of the carbon black type polylactic acid conductive masterbatch is less than 20Ω·cm, and the resistivity of the metal oxide type polylactic acid conductive masterbatch is less than 2000Ω·cm.
[0011] In order to solve the problems of poor toughness, lack of elasticity, high brittleness, slow crystallization rate and low melt strength of polylactic acid materials, which make it difficult to produce highly conductive polylactic acid conductive masterbatch that can be used to manufacture polylactic acid conductive fibers through composite spinning process, low melting point branched polylactic acid is used. It has good fluidity and good compatibility with polylactic acid body and conductive agent.
[0012] The branched polylactic acid is prepared by the following preparation method: a modification aid Lewis acid, an acrylate monomer and polylactic acid are mixed, melt blended and reacted in a screw extruder or an internal mixer, and then extruded. The modification aid is added in an amount of 0.5-5 parts of Lewis acid per 100 parts of polylactic acid, and 1-6 parts of acrylate monomer.
[0013] Specifically, the preparation method of branched polylactic acid is as follows: a Lewis acid such as magnesium chloride, ferric chloride, calcium chloride, aluminum chloride, carbendazim or zinc chloride, an acrylate monomer such as trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated glycerol triacrylate or pentaerythritol triacrylate, etc., is mixed with polylactic acid, melt blended and reacted in a screw extruder or internal mixer, and then extruded to obtain the obtained product. The melting point and the degree of branching of the product are mainly determined by the addition amount of the Lewis acid and the branching auxiliary agent. For example, when preparing low-melting-point branched polylactic acid, the addition amount of the Lewis acid is 3-5 parts and the acrylate monomer is 3-6 parts per 100 parts of polylactic acid; when preparing branched polylactic acid, the acrylate monomer is 1-3 parts and the addition amount of the Lewis acid is 0.5-1.5 parts.
[0014] A method for preparing a polylactic acid conductive masterbatch comprises the following steps: Step 1: Dry the conductive powder at 95°C, put the dried conductive powder into a high-speed mixer, add a coupling agent, and heat to 125°C. After high-speed stirring for 25 minutes, add a dispersing modifier, an antioxidant, and a lubricant respectively, and mix at high speed; Step 2: High-speed hot mixing of the material obtained in step 1 and polylactic acid powder for 15 minutes at a temperature of 95-105°C, and then high-speed cold mixing for 15 minutes to discharge the material; the obtained material is put into the loss-in-weight weighing hopper of a twin-screw extruder, and under the condition of quantitative and uniform feeding, it enters the twin-screw extruder for shearing and dispersion, and then cold water strips are drawn and pelletized to obtain polylactic acid conductive masterbatch, with an extrusion temperature of 180-220°C, a screw speed of 100-350 rpm, and a water bath cooling temperature of 15~35°C.
[0015] A polylactic acid conductive fiber, the polylactic acid conductive fiber is a two-component composite structure, including 10-30% of a conductive component and 70-90% of a non-conductive component, the conductive component is a polylactic acid conductive masterbatch, and the non-conductive component is a polylactic acid slice added with branched polylactic acid, wherein the content of branched polylactic acid is 0-5%; the fiber cross section is a composite structure, the fiber strength is 2-2.8 cN / dtex, the elongation at break is 30-150%, and the electrical resistance is 10 5-10 Ω / cm, among which the conductive fiber made of carbon black polylactic acid conductive masterbatch has a resistance of 10 5-7 Ω / cm, the resistance of the conductive fiber made of metal oxide polylactic acid conductive masterbatch is 10 7 -10 Ω / cm.
[0016] Preferably, the polylactic acid conductive fibers are polylactic acid FDY conductive filaments, polylactic acid curled conductive filaments, and polylactic acid conductive staple fibers or wool strips.
[0017] A method for preparing polylactic acid conductive fiber adopts a two-component composite spinning process, and further adopts a texturing process to prepare polylactic acid curled and deformed conductive fiber, and a drawing and cutting process to prepare polylactic acid conductive staple fiber or wool strip.
[0018] Composite spinning process: The two types of slices are added to their respective screw feed ports respectively, and enter the respective melt channels of the two-component composite spinning assembly through screw extrusion and metering pumps. After merging at the fusion plate, they are ejected from the spinneret, cooled by side blowing, bundled and oiled, drawn, guided and wound, inspected, and put into storage.
[0019] Since the ester bonds are easily degraded during polyester spinning, it is necessary to control the moisture content of the chips. In the spinning process, the moisture content of the non-functional component chips is controlled below 50 ppm, preferably below 30 ppm, and the moisture content of the functional component chips is controlled below 80 ppm, preferably below 40 ppm.
[0020] The melt stream ejected from the spinneret is cooled by wind and solidified into nascent fibers, wherein the side blowing wind pressure is 50-500Pa, the wind speed is 0.4-1.0m / s; the wind temperature is 15-25℃, and the wind humidity is 65%-80%. After the nascent fiber bundle is oiled by a special oil agent through the guide wire, it passes through the tunnel to the winding process, and after the upper and lower guide wire discs change the direction and adjust the tension, it enters the winder to be wound into a silk cake, and the drawing and winding speed is 2500-4500m / min. The fiber obtained here has a large elongation, and can also be obtained by secondary low-speed drawing and shaping to obtain polylactic acid conductive drawn yarn; and the polylactic acid conductive stretched yarn with better weaving performance can be obtained by drawing and curling through a texturing machine; and the polylactic acid conductive staple fiber can be obtained by bundling, for example, bundling to 1 million deniers (D) for drawing, curling and cutting.
[0021] Preferably, the polylactic acid can be L-polylactic acid, D-polylactic acid, or racemic polylactic acid.
[0022] Preferably, the polylactic acid slices are commercial fiber-grade polylactic acid slices.
[0023] A fiber aggregate comprises the fiber aggregate of the polylactic acid conductive fiber.
[0024] The method for determining the resistance of the product in this application is described as follows: Conductive masterbatch is similar to conventional spinning chips or commercially available chips, and is generally an irregular cylinder with a diameter of 2-3mm and a height of 2.5-3.5mm. The resistance of the masterbatch is measured by using the resistance range of a multimeter, manually pressing the measuring head in a symmetrical position in the diameter direction of the cylinder to read the reading.
[0025] Conductive masterbatch resistivity determination: The conductive melt obtained when measuring the melt index is manually drawn to obtain 0.05-0.2mm wire strips, and the resistance value is measured with a high resistance meter or a multimeter, and the resistivity is calculated according to the resistance formula R=pL / s.
[0026] The resistance of the conductive fiber bundle is measured by using a high resistance meter with a 10 cm measuring clamp spacing. The conductive fiber bundle is clamped on the clamp head, and the high resistance meter reading is read and divided by 10 to obtain the fiber bundle resistance in Ω / cm.
[0027] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention adopts low-melting-point branched polylactic acid as the dispersant and compatibilizer of polylactic acid conductive masterbatch, which has good fluidity and good compatibility with polylactic acid body and conductive agent, thus solving the fluidity and spinnability problems of polylactic acid conductive masterbatch. Due to the good dispersion effect of conductive agent, the masterbatch has low resistance.
[0028] 2. When spinning polylactic acid conductive fibers, adding an appropriate amount of branched polylactic acid to the non-conductive component can improve the effect of spinning orientation and stretching, making the composite spinning process normal. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a schematic cross-sectional view of a three-leaf outer conductive fiber of the present invention; Figure 2 It is a schematic cross-sectional view of the straight inner guide fiber of the present invention. DETAILED DESCRIPTION
[0030] The present invention will be further described below.
[0031] Example 1: Carbon black polylactic acid conductive masterbatch and preparation method The weight of each component of the carbon black polylactic acid conductive masterbatch: 6.45 kg of polylactic acid powder, 3.15 kg of carbon black conductive powder, 50 g of aluminate coupling agent, 300 g of low melting point branched polylactic acid, 20 g of 1010 antioxidant, and 30 g of stearyl magnesium lubricant.
[0032] Preparation method: Step 1, drying carbon black conductive powder at 95°C for 6 hours, placing the dried conductive powder into a high-speed mixer, adding an aluminate coupling agent, and heating to 125°C, stirring at high speed for 25 minutes, and then adding low-melting point branched polylactic acid, 1010 antioxidant and magnesium stearate lubricant, respectively, and mixing at high speed; Step 2, add polylactic acid powder, continue high-speed hot mixing for 15 minutes, the temperature is 95°C, and then high-speed cold mixing for 15 minutes to discharge; the obtained material is put into the weight loss hopper of the twin-screw extruder, and the material is evenly discharged at a feeding rate of 10 kg per hour, and enters the Φ25 twin-screw extruder for shearing and dispersion, and then cold water pulls the strips and pelletizes them to obtain polylactic acid conductive masterbatch. The extrusion temperature is 180°C in zone 1, 210°C in zone 2, 215°C in zone 3, 215°C in zone 4, 215°C in zone 5, 215°C in zone 6, 215°C in zone 7, and 215°C in zone 8. The die head is 220°C, the screw speed is 250 rpm, and the water bath cooling temperature is 25°C.
[0033] Results: The single-particle resistance of the prepared polylactic acid conductive masterbatch was 45Ω, and the melt index measured at 230℃ and 2.16 kg was 95g / 10min.
[0034] Example 2: Metal oxide type polylactic acid conductive masterbatch and preparation method The weight of each component of the metal oxide type polylactic acid conductive masterbatch: 3.45 kg of polylactic acid powder, 6.2 kg of 521W metal oxide conductive powder, 50 g of aluminate coupling agent, 250 g of low melting point branched polylactic acid, 20 g of 1010 antioxidant, and 30 g of magnesium stearate lubricant.
[0035] Preparation method: Step 1, drying 521W metal oxide conductive powder at 95°C for 6 hours, placing the dried conductive powder into a high-speed mixer, adding an aluminate coupling agent, and heating to 135°C, stirring at high speed for 20 minutes, and then adding low melting point branched polylactic acid, 1010 antioxidant and magnesium stearate lubricant, respectively, and mixing at high speed; Step 2, add polylactic acid powder, continue high-speed hot mixing for 15 minutes, the temperature is 90°C, and then high-speed cold mixing for 15 minutes to discharge; the obtained material is put into the weight loss hopper of the twin-screw extruder, and the material is evenly discharged at a feeding rate of 15 kg per hour, and enters the Φ25 twin-screw extruder for shearing and dispersion, and then cold water strips are drawn and pelletized to obtain polylactic acid conductive masterbatch, the extrusion temperature is 180°C in zone 1, 205°C in zone 2, 210°C in zone 3, 210°C in zone 4, 210°C in zone 5, 210°C in zone 6, 210°C in zone 7, 210°C in zone 8, the die head is 205°C, the screw speed is 300 rpm, and the water bath cooling temperature is 25°C.
[0036] Results: The single-particle resistance of the prepared polylactic acid conductive masterbatch was 950Ω, and the melt index measured at 230℃ and 2.16 kg was 125 g / 10 min.
[0037] Example 3: Preparation of composite spinning carbon black type polylactic acid conductive fiber A two-component composite spinning production line is used, and carbon black type polylactic acid conductive masterbatch is used as the conductive component, which is melted by the masterbatch screw and metered by the metering pump; polylactic acid slices are non-conductive components, which are melted by the slice screw, and branched polylactic acid slices are evenly added to the polylactic acid slice feed port through a syringe, wherein the branched polylactic acid content is 3% relative to the polylactic acid; the fiber cross section adopts a three-leaf outer guide shape ( Figure 1 ), screw extrusion temperature 215℃, spinning box temperature 220℃, side blowing temperature 22℃, wind speed 0.6m / s, oiling amount 0.8%, winding speed 3500m / min. 20D / 4f three-leaf external conductive polylactic acid conductive fiber was obtained, with a fiber strength of 2.35cN / dtex, a breaking elongation of 65%, and a bundle resistance of 5×10 6 Ω / cm.
[0038] Further low-speed drawing, hot plate temperature 85 ° C, hot plate temperature 120 ° C, drawing speed 500 m / min, drawing 1.2 times, carbon black type polylactic acid conductive drawn yarn was obtained, the fiber strength was 2.75 cN / dtex, the elongation at break was 35%, and the yarn resistance was 2×10 6 Ω / cm.
[0039] Example 4: Preparation of metal oxide-based polylactic acid conductive fibers by composite spinning A two-component composite spinning production line is used, and metal oxide polylactic acid conductive masterbatch is used as the conductive component. The conductive masterbatch enters the masterbatch screw for melting and is metered by a metering pump; the polylactic acid slice is a non-conductive component, which is melted by the slice screw, and the branched polylactic acid slice is evenly added to the polylactic acid slice feed port through a syringe, wherein the branched polylactic acid content is 2.5% relative to the polylactic acid; the fiber cross section adopts a straight inner guide shape ( Figure 2 ), screw extrusion temperature 215℃, spinning box temperature 220℃, side blowing temperature 22℃, wind speed 0.5m / s, oiling amount 1.0%, winding speed 3100m / min. The obtained 60D / 6f straight inner-conducting polylactic acid POY fiber has a fiber strength of 2.05cN / dtex, a breaking elongation of 125%, and a bundle resistance of 6×10 9 Ω / cm.
[0040] The conductive POY (pre-oriented yarn) fiber was further drawn at a low speed, with a hot plate temperature of 80°C, a hot plate temperature of 115°C, a drawing speed of 500 m / min, and a drawing of 1.5 times to obtain a 40D / 6f metal oxide type polylactic acid conductive drawn yarn (a light-colored conductive fiber, usually called white conductive fiber), with a fiber strength of 2.95 cN / dtex, an elongation at break of 38%, and a bundle resistance of 1×10 9 Ω / cm.
[0041] The conductive POY (pre-oriented yarn) fiber was further stretched by a texturing machine with a drafting multiple of 1.5, a process speed of 500 m / min, a first hot box temperature of 135 °C, and a second hot box temperature of 105 °C to obtain a 40D / 6f curled metal oxide type polylactic acid conductive stretched yarn with a fiber strength of 3.0 cN / dtex, an elongation at break of 35%, and a bundle resistance of 8×10 8 Ω / cm.
[0042] Comparative Example 1: The weight of each component of the raw materials: 6.45 kg of polylactic acid powder, 3.15 kg of carbon black conductive powder, 50 g of aluminate coupling agent, 300 g of dispersant TS-2A, 20 g of 1010 antioxidant, and 30 g of magnesium stearate lubricant.
[0043] Preparation method: Step 1, dry 3.15 kg of carbon black conductive powder at 95°C for 6 hours, put the dried conductive powder into a high-speed mixer, add 50 g of aluminate coupling agent, and heat to 125°C. After high-speed stirring for 25 minutes, add 300 g of dispersant TS-2A, 20 g of 1010 antioxidant and 30 g of magnesium stearate lubricant respectively, and mix at high speed; Step 2: Add polylactic acid powder, continue high-speed hot mixing for 15 minutes at a temperature of 95°C, and then high-speed cold mixing for 15 minutes to discharge the material; put the obtained material into the loss-in-weight weighing hopper of the twin-screw extruder, feed it evenly at a feeding rate of 10 kg per hour, enter the Φ25 twin-screw extruder for shearing and dispersion, then draw strips in cold water and cut into pellets to obtain polylactic acid conductive masterbatch.
[0044] The single-particle resistance of the prepared masterbatch is 500Ω, and the melt index measured at 230°C and 2.16 kg is 55 g / 10 min. The large resistance of the masterbatch indicates that the conductive carbon black is not well dispersed.
[0045] Spinning: A two-component composite spinning production line is used, using carbon black type polylactic acid conductive masterbatch as the conductive component, which is melted through the masterbatch screw and metered by a metering pump; polylactic acid chips are non-conductive components, which are melted through the chip screw. A three-leaf outer guide spinning assembly is used, the screw extrusion temperature is 215℃, and the spinning box temperature is 220℃. The primary fiber can be sprayed out from the spinneret, but it is difficult to suck the gun and the spinning fails.
[0046] The above embodiments of the present invention are merely examples to clearly illustrate the present invention, but are not intended to limit the protection scope of the present invention. All equivalent technical solutions also belong to the scope of the present invention. The patent protection scope of the present invention should be defined by the claims.
Claims
1. A polylactic acid conductive masterbatch, characterized in that: The polylactic acid conductive masterbatch is prepared from raw materials including polylactic acid powder, conductive powder, coupling agent, dispersing modifier, antioxidant and lubricant, and the polylactic acid conductive masterbatch includes carbon black type polylactic acid conductive masterbatch and metal oxide type polylactic acid conductive masterbatch; The carbon black type polylactic acid conductive masterbatch comprises polylactic acid powder, conductive carbon black powder, aluminate coupling agent, dispersing modifier, 1010 antioxidant, and stearic magnesium lubricant, and the weight percentage of each component is: polylactic acid powder 60-75%, conductive carbon black powder 20-35%, aluminate coupling agent 0.2-1%, dispersing modifier 2-6%, 1010 antioxidant 0.1-0.5%, and stearic magnesium lubricant 2-4%; The metal oxide type polylactic acid conductive masterbatch comprises polylactic acid powder, conductive metal oxide powder, aluminate coupling agent, dispersing modifier, 1010 antioxidant, and magnesium stearate lubricant, and the weight percentage of each component is: polylactic acid powder 25-45%, conductive metal oxide powder 50-70%, aluminate coupling agent 0.2-1%, dispersing modifier 1-4%, 1010 antioxidant 0.1-0.5%, magnesium stearate lubricant 1-2%; The dispersing modifier adopts low melting point branched polylactic acid, the resistivity of carbon black type polylactic acid conductive masterbatch is less than 20Ω·cm, and the resistivity of metal oxide type polylactic acid conductive masterbatch is less than 2000Ω·cm; The branched polylactic acid is prepared by the following preparation method: a modification aid Lewis acid, an acrylate monomer and polylactic acid are mixed, melt blended and reacted in a screw extruder or an internal mixer, and then extruded to obtain the branched polylactic acid. The modification aid is added in an amount of 0.5-5 parts of Lewis acid per 100 parts of polylactic acid, and 1-6 parts of acrylate monomer.
2. A method for preparing a polylactic acid conductive masterbatch according to claim 1, characterized in that: The steps include: Step 1: Dry the conductive powder at 95°C, put the dried conductive powder into a high-speed mixer, add a coupling agent, and heat to 125°C. After high-speed stirring for 25 minutes, add a dispersing modifier, an antioxidant, and a lubricant respectively, and mix at high speed; Step 2: High-speed hot mixing of the material obtained in step 1 and polylactic acid powder for 15 minutes at a temperature of 95-105°C, and then high-speed cold mixing for 15 minutes to discharge the material; the obtained material is put into the loss-in-weight weighing hopper of a twin-screw extruder, and under the condition of quantitative and uniform feeding, it enters the twin-screw extruder for shearing and dispersion, and then cold water strips are drawn and pelletized to obtain polylactic acid conductive masterbatch, with an extrusion temperature of 180-220°C, a screw speed of 100-350 rpm, and a water bath cooling temperature of 15~35°C.
3. A polylactic acid conductive fiber, characterized in that: The polylactic acid conductive fiber is a two-component composite structure, including 10-30% of a conductive component and 70-90% of a non-conductive component, wherein the conductive component is the polylactic acid conductive masterbatch according to any one of claims 1 to 2, and the non-conductive component is a polylactic acid slice added with branched polylactic acid, wherein the content of branched polylactic acid is 0-5%; the fiber cross section is a composite structure, the fiber strength is 2-2.8 cN / dtex, the elongation at break is 30-150%, and the electrical resistance is 10 5 -10 10 Ω / cm, among which the conductive fiber made of carbon black polylactic acid conductive masterbatch has a resistance of 10 5 -10 7 Ω / cm, the resistance of the conductive fiber made of metal oxide polylactic acid conductive masterbatch is 10 7 -10 10 Ω / cm.
4. The polylactic acid conductive fiber according to claim 3, characterized in that: The polylactic acid conductive fibers are polylactic acid FDY conductive filaments, polylactic acid curled deformed conductive filaments, and polylactic acid conductive staple fibers or wool strips.
5. A method for preparing the polylactic acid conductive fiber according to any one of claims 3 to 4, characterized in that: The polylactic acid conductive fibers are prepared by a two-component composite spinning process, and a stretching process is further used to obtain polylactic acid curled and deformed conductive fibers, and a drawing and cutting process is used to obtain polylactic acid conductive staple fibers or wool strips.
6. A fiber aggregate, characterized in that: A fiber aggregate comprising the polylactic acid conductive fibers as described in claims 3-4.
Citation Information
Patent Citations
Conducting fiber of composite structure and preparation method thereof
CN106884315A
Branched polylactic acid with low melting point and preparation method of branched polylactic acid
CN108359087A
Self-crimping conductive fiber and preparation method thereof
CN108560079A
Preparation method of biological organic fertilizer
CN109970489A
Polylactic acid material used for 3D printing supplies and preparation method of polylactic acid material
CN110144101A